Carboxylesterase-involved metabolism of di-n-butyl phthalate in pumpkin (Cucurbita moschata) seedlings. (January 2017) - Lin, Qingqi; Chen, Siyuan; Chao, Yuanqing; Huang, Xiongfei; Wang, Shizhong; Qiu, Rongliang
Abstract: Uptake and accumulation by plants is a significant pathway in the migration and transformation of phthalate esters (PAEs) in the environment. However, limited information is available on the mechanisms of PAE metabolism in plants. Here, we investigated the metabolism of di- n -butyl phthalate (DnBP), one of the most frequently detected PAEs, in pumpkin ( Cucurbita moschata ) seedlings via a series of hydroponic experiments with an initial concentration of 10 mg L −1 . DnBP hydrolysis occurred primarily in the root, and two of its metabolites, mono- n -butyl phthalate (MnBP) and phthalic acid (PA), were detected in all plant tissues. The MnBP concentration was an order of magnitude higher than that of PA in shoots, which indicated MnBP was more readily transported to the shoot than was PA because of the former's dual hydrophilic and lipophilic characteristics. More than 80% of MnBP and PA were located in the cell water-soluble component except that 96% of MnBP was distributed into the two solid cellular fractions (i.e., cell wall and organelles) at 96 h. A 13–20% and 29–54% increase of carboxylesterase (CXE) activity shown in time-dependent and concentration-dependent experiments, respectively, indicated the involvement of CXEs in plant metabolism of DnBP. The level of CXE activity in root subcellular fractions was in the order: the cell water-soluble component (88–94%) >> cell wall (3–7%) > cell organelles (3–4%), suggesting that the cell water-soluble component is the dominant locus of CXE activity and also the domain of CXE-catalyzed hydrolysis of DnBP. The addition of triphenyl phosphate, a CXE inhibitor, led to 43–56% inhibition of CXE activity and 16–25% increase of DnBP content, which demonstrated the involvement of CXEs in plant metabolism of DnBP. This study contributes to our understanding of enzymitic mechanisms of PAE transformation in plants. Graphical abstract: Highlights: Mono- n -butyl phthalate and phthalic acid are phase I metabolites of DnBP in pumpkin. Carboxylesterases (CXEs) are involved in the metabolism of DnBP. The cell water-soluble component is the primary site of CXE activity. The cell water-soluble component is the metabolic domain of DnBP hydrolysis. Abstract : Hydrolysis of di- n -butyl phthalate takes place mainly in the cell water-soluble component and mono- n -butyl phthalate and phthalic acid are the phase I metabolites.